Julian the Apostate at Antioch - Downey, Glanville (Church history, 1939)
Few figures in the story of the rise and establishment of Christianity have drawn so much attention as Julian the Apostate. The emperor who attempted to overthrow the church and reestablish the ancient pagan faith has from his own day to this been bitterly attacked by some, and as stoutly defended by others, until he has become almost a legendary character. Whether monster or tragic hero, his brief career has inevitably called forth an enormous literature in which every shade of the Christian and the pagan points of view is represented. Professional scholars and men of letters, attracted by a number of different aspects of the emperor's life, find rich material in the problem of his curiously mixed personality and in the spectacle of this last concerted; attempt to revive dying paganism. The manner in which the pagans responded to the attempt, and the way in which the church combatted this attack upon it, are alike subjects which will seem to every student to offer valuable lessons. Scholars realize both the difficulty and the importance of a just appreciation of these problems, and the effort to assay them properly has produced studies of the highest value.